Occipital neuralgia in lung carcinoma: a rare clinical scenario case report - Dhar, Sovan Sarang; Sahoo, Rajendra; Khan, Zulfuqur Hossain; Das Majumdar, Saroj Kumar; Parida, Dillip Kumar (Archive of Oncology, 2018)
Occipital neuralgia is an uncommon cause of pain over occipital region. When occipital nerves are affected due to osteogenic / vasculogenic / neurogenic causes it is manifested as a sharp shooting or stabbing type of pain over the occipital region of scalp, often progressing to involve the vertex and the temporal region as well. Use and withdrawal of variety of drugs result in headache. The role of any chemotherapeutic drug, as a causative agent for occipital neuralgia, has not been described in literature so far. We are reporting a rare case of occipital neuralgia precipitated while on combination chemotherapy regimen in lung carcinoma.